DEVELOPMENT OF WORK PROGRAMS IMPROVEMENT THROUGH MANAGEMENT SUPERVISION OF SCHOOL PRINCIPLES - Irawati Hasan (LPPM Ekasakti University, 2022)
As a manager, the principal is faced with many tasks that require serious responsibility in its implementation. This School Action Research (PTS) was carried out at State Elementary Schools 08 Marunggi and the problem studied is the Principal's Work Program in the managerial field, especially in the preparation of the principal's annual work program through the Principal's Managerial Supervision by the School Supervisor which is followed up with direct and continuous guidance and coaching. In the implementation of this PTS, the procedures are to supervise and analyze the administration of the principal, provide technical guidance on SWOT analysis and ways of preparing the annual work program and direct the making of a SWOT analysis and the preparation of the principal's annual work program.